Oxidative insults disrupt OPA1-mediated mitochondrial dynamics in cultured mammalian cells - Iraselia Garcia; Wendy Innis-Whitehouse; Alma Lopez; Megan Keniry; Robert Gilkerson (Taylor & Francis Group, 2018)
Objective: To explore the impact of oxidative insults on mitochondrial dynamics. In mammalian cells, oxidative insults activate stress response pathways including inflammation, cytokine secretion, and apoptosis. Intriguingly, mitochondria are emerging as a sensitive network that may function as an early indicator of subsequent cellular stress responses. Mitochondria form a dynamic network, balancing fusion, mediated by optic atrophy-1 (OPA1), and fission events, mediated by dynamin-related protein-1 (DRP1), to maintain homeostasis. Methods: Here, we examine the impact of oxidative insults on mitochondrial dynamics in 143B osteosarcoma and H9c2 cardiomyoblast cell lines via confocal microscopy, flow cytometry, and protein-based analyses. Results: When challenged with hydrogen peroxide (H2O2), a ROS donor, both cell lines display fragmentation of the mitochondrial network and loss of fusion-active OPA1 isoforms, indicating that OPA1-mediated mitochondrial fusion is disrupted by oxidative damage in mammalian cells. Consistent with this, cells lacking OMA1, a key protease responsible for cleavage of OPA1, are protected against OPA1 cleavage and mitochondrial fragmentation in response to H2O2 challenge. Discussion: Taken together, these findings indicate that oxidative insults damage OPA1-mediated mitochondrial dynamics in mammalian cells via activation of OMA1, consistent with an emerging role for mitochondrial dynamics as an early indicator of cellular stress signaling. Abbreviations: Δψm: transmembrane potential; ROS: reactive oxygen species; H2O2: hydrogen peroxide; OPA1: optic atrophy-1; MFN1: mitofusin1; DRP1: dynamin-related protein 1; DMEM: Dulbecco's Modified Eagle's Medium; PBS: phosphate buffer saline; TOM20: translocase of the outer mitochondrial membrane-20; DAPI: diaminophenylindole; TMRE: tetramethylrhodamine ethyl ester; TBST: Tris-Buffered Saline Tween-20; MEF: mouse embryonic fibroblast.